Uji Coba Pemberian Snack Bars Berbahan Dasar Tape Ketan Hitam sebagai Sumber Serat terhadap Penurunan Kadar Glukosa Darah Puasa Pasien Diabetes Melitus Tipe 2 - Billah, Muhammad Muayyad; Wiboworini, Budiyanti; Prayitno, Adi (Jurnal Penyakit Dalam Indonesia, 2023)
Introduction. Managing dietary pattern, including snack schedule, is one of the most important factors in maintaining blood glucose levels in patients with type 2 diabetes mellitus (T2DM). Black glutinous rice tape is one of the foods that contains bioactive nutrient and fiber beneficial to health. This study aimed to determine the effect of snack bars made from black glutinous rice tape on fasting blood glucose levels in T2DM patients. Methods. The study employed a quasi-experimental pre and post-test design with a control group which was conducted among T2DM patients undergoing treatment at Bhayangkara Tk. II Sartika Asih Hospital, Bandung. The study was conducted from October 2022 to January 2023 and involved a total of 22 subjects divided into two groups (treatment and control), selected through the accidental sampling method. The treatment group received a daily intake of 3 x 30 grams sticky rice tape snack bar for 7 days along with nutritional counseling, while the control group did not received the snack bar but received nutritional counseling. Fasting blood glucose (FBG) levels were measured both before and after treatment, then analyzed using a paired sample T-test. The difference in the treatment’s impact between the two groups was assessed using the Wilcoxon test. Results. Statistical analysis showed a reduction in the mean levels of FBG in the control group by 21.36 mg/dL (p=0.111) and in the treatment group by 61.46 mg/dL (p=0.021). There was an impact of consuming black glutinous rice tape snack bars on the reduction of FBG levels in DMT2 patients, with a difference in FBG reduction between the control and treatment groups of 40.10 mg/dL (p=0.018). Conclusion. Administering 3 x 30 grams of black sticky rice tape snack bars for 7 days was effective in reducing the FBG levels in T2DM patients.